Resilience Factors, the School-Based Universal Prevention Program “Unplugged” and Healthy Behavior among Early Adolescents - Abrinkova, Lenka; Orosová, Oľga; De Jesus, Saul Neves; Gajdošová, Beata; Bacikova-Sleskova, Maria (European Journal of Mental Health, 2021)
The paper investigates the role of the internal asset (IA), perceived external resources (PER) of resilience, and the school-based universal prevention program known as ‘Unplugged’ in explaining persistent healthy behavior among early adolescence. A sample of 425 adolescents was collected in a repeated measure design study with a baseline (T1) and a six-month follow-up (T2) after the Unplugged implementation. Persistent healthy behavior was assessed by a change in the cumulative index of substance use created by combining alcohol use and cigarette smoking in the past 30 days and their change between T1 and T2. Four categories were created: non-users, permanent users, new users and ex-users. A multinominal logistic regression revealed that non-users were more likely to show higher self-esteem when compared to permanent users. Females had a higher probability of being non-users than either being permanent users or new users. Moreover, Unplugged intervention increased the probability of being a non-user rather than a new user. Regarding PER of resilience, non-users were more likely to have higher home support, prosocial peers, and school connectedness compared to permanent users. Non-users were also more likely to have higher levels of prosocial peers compared to new users. In summary, higher self-esteem, home support, prosocial peers and school connectedness are associated with persistent healthy behavior. To maintain this persistent healthy behavior, the school-based universal prevention program Unplugged has been effective; thus internal assets and external resources of resilience, and prevention program Unplugged, play an important role in the absence of alcohol or cigarette use in early teenage years.